Coating agent and packaging material

The coating agent, composed of a high-modulus binder resin, fine particles, and a solvent, addresses the limitations of conventional agents by providing superior heat resistance, adhesion, and transparency for packaging materials, particularly in bag production and heat sealing.

JP2025056676APending Publication Date: 2025-04-08TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023166290
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Conventional coating agents for packaging materials lack sufficient heat resistance, suitability for bag production, adhesion, and transparency, particularly during the heat sealing process.

Method used

A coating agent comprising a binder resin with a high storage modulus, fine particles such as calcium carbonate or barium sulfate, and a solvent, which together form a coating layer with excellent heat resistance, adhesion, and transparency, while maintaining a low viscosity for easy printing.

Benefits of technology

The coating agent effectively suppresses heat shrinkage and ensures excellent adhesion and transparency, making it suitable for bag production and heat sealing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056676000003
    Figure 2025056676000003
  • Figure 2025056676000004
    Figure 2025056676000004
  • Figure 2025056676000001
    Figure 2025056676000001
Patent Text Reader

Abstract

To provide a coating agent capable of forming a coating layer having excellent heat resistance, suitability for bag making, adhesion, and transparency.SOLUTION: The coating agent comprises a binder resin, fine particles, and a solvent, wherein the storage modulus of the binder resin at 110°C, as measured according to JIS K 7244-4, is 1.0×108 Pa or more, and the viscosity of the coating agent, when the solid content is 26 mass%, as measured according to JIS K 7117-1, is 1,000 mPa s or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating agent capable of forming a coating layer that is excellent in heat resistance, suitability for bag making, adhesion, and transparency, and to a packaging material using the same. [Background technology]

[0002] Packaging bags for flexible packages are made by combining multiple types of plastics, using biaxially oriented films such as polypropylene and polyester to obtain mechanical strength, and polyethylene, polypropylene, ethylene-vinyl acetate copolymer, etc. as heat-sealing materials to seal the contents. The above material selection was made with an emphasis on suitability during use, such as packaging of contents, transportation, storage, opening, etc. However, in recent years, with the growing awareness of environmental issues, importance has been placed on resource conservation and recyclability of various products.

[0003] In the bag making process for forming packaging bags, the packaging material is folded so that the sealant layers overlap, and the packaging material is heat sealed by applying pressure from the outer surface side of the base layer with a high-temperature tool. The tool of the heat sealing machine is hot, and the outer surface side of the base layer that directly contacts the tool is exposed to high temperatures. If the packaging material has low heat resistance, the base layer may be affected by the heat, causing thermal shrinkage of the heat-sealed part and / or a phenomenon in which the heat-sealed part is cut off from the packaging material (melting), resulting in insufficient suitability for bag making. Therefore, there is a need for the development of a coating agent that can impart suitability for bag making to packaging materials.

[0004] Patent documents 1, 2, and 3 describe coating agents containing nitrocellulose resin and fine particles, but the viscosity of the coating agents is high, and when they are diluted to a viscosity suitable for printing, the solid content decreases, making it impossible to obtain a film thickness required for performance, and the above-mentioned thermal shrinkage cannot be sufficiently suppressed. Patent Document 4 describes an invention related to a coating agent containing nitrocellulose resin, urethane resin, and silica particles. However, the coating agent contains a large amount of urethane resin, which causes problems with heat resistance during heat sealing and suitability for bag making. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-171910 A [Patent Document 2] JP 2015-101688 A [Patent Document 3] JP 2018-70847 A [Patent Document 4] JP 2015-214673 A Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, conventional coating agents are inferior in heat resistance and suitability for bag making, and furthermore do not satisfy the adhesion and transparency required for packaging materials.

[0007] Therefore, an object of the present invention is to provide a coating agent capable of forming a coating layer having excellent heat resistance, suitability for bag making, adhesion, and transparency. [Means for solving the problem]

[0008] As a result of extensive research into the above problems, the present inventors have found that the above problems can be solved by the coating agent described below, and have thus completed the present invention.

[0009] That is, the present invention relates to the following [1] to

[12] .

[0010] [1] A coating agent comprising a binder resin, fine particles and a solvent, wherein the binder resin has a storage modulus of 1.0×10 Pa or more at 110°C as measured in accordance with JIS K 7244-4, and a viscosity of 1,000 mPa s or less as measured in accordance with JIS K 7117-1 when the solid content of the coating agent is 26 mass%.

[0011] [2] The coating agent according to [1], wherein the binder resin has a loss modulus at 100°C measured in accordance with JIS K 7244-4 of 1.0 x 108 Pa or more.

[0012] [3] The coating agent according to [1] or [2], wherein the fine particles are inorganic fine particles.

[0013] [4] The coating agent according to [3], wherein the inorganic fine particles contain at least one selected from the group consisting of calcium carbonate, barium sulfate, titanium oxide, zinc oxide, aluminum oxide, and zirconium oxide.

[0014] [5] The coating agent according to any one of [1] to [4], wherein the average particle diameter of fine particles measured by a laser light scattering method is 3,000 nm or less.

[0015] [6] The coating agent according to any one of [1] to [5], wherein a mass ratio of the fine particles to 100 mass% of the binder resin is 1 to 900 mass%.

[0016] [7] The coating agent according to any one of [1] to [6], wherein the binder resin contains a cellulose-based resin.

[0017] [8] The coating agent according to any one of [1] to [7], wherein the solvent comprises a glycol-based solvent.

[0018] [9] The coating agent according to any one of [1] to [8], further comprising a chlorinated polyolefin.

[0019]

[10] The coating agent according to any one of [1] to [9], which is used for suppressing thermal shrinkage of a substrate.

[0020]

[11] A packaging material having a coating layer made of the coating agent according to any one of [1] to

[10] on a substrate 1.

[0021] 3. A packaging material comprising a substrate 1, an adhesive layer and a substrate 2 in this order, and further comprising a coating layer made of the coating agent according to claim 1 or 2. Effect of the Invention

[0022] According to the present invention, it is possible to provide a coating agent capable of forming a coating layer that is excellent in heat resistance, suitability for bag making, adhesion, and transparency. [Brief description of the drawings]

[0023] [Figure 1] This is a diagram in which a laminate cut into a size of 50 mm x 25 mm is heated and pressed in an area of ​​20 mm x 10 mm, with the area before heating and pressing being shown shaded. [Diagram 2] This is a diagram in which a laminate cut to a size of 50 mm x 25 mm is heated and pressed in an area of ​​20 mm x 10 mm, and the area after heating and pressing is shown by shading. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The following describes in detail the embodiments of the present invention. However, the following description of the components is merely an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0025] <Coating agent> The present invention relates to a coating agent comprising a binder resin, fine particles and a solvent, the binder resin having a storage modulus at 110° C. measured according to JIS K 7244-4 of 1.0×10 8 The coating agent is characterized in that the viscosity, measured according to JIS K 7117-1, of the coating agent is 1,000 mPa·s or less when the solid content of the coating agent is 26% by mass. The coating agent is printed on a substrate by a known printing method, and a coating layer can be formed by removing the volatile components. The coating agent of the present invention and the coating layer formed using the coating agent are preferably free of chromatic color, but this does not exclude those containing a small amount of colorant unintentionally mixed in.

[0026] The main use of the coating agent of the present invention is preferably for suppressing thermal shrinkage of a substrate subjected to an external stimulus due to heat, and more preferably for suppressing thermal shrinkage of a packaging material. The use is not limited to the above, and the coating agent can also be used for protecting the packaging material itself or its surface, the ink layer contained in the packaging material, the barrier layer, etc. from external stimuli such as dirt, scratches, impact, moisture, oil, and heat. The surface to which the coating agent of the present invention is applied is not particularly limited, and the coating layer obtained by applying the coating agent may be present as the outermost layer of the packaging material or as an inner layer of the packaging material, but is preferably in contact with the substrate.

[0027] The coating agent of the present invention contains a binder resin and fine particles that have a high storage modulus even at high temperatures, and the binder resin is adsorbed to the surface of the fine particles, which allows the formation of a hard coating film and reduces the viscosity of the coating agent. This makes it possible to reduce the viscosity of the coating agent to 1,000 mPa·s or less when the solid content of the coating agent is 26% by mass, and by printing with a high solid content in particular, it is possible to increase the density of the coating film and increase the film thickness, even though the coating film is hard, and therefore it is possible to form a coating film that is excellent in heat resistance, suitability for bag making, and adhesion. However, the above is based on scientific considerations, and the present invention is not limited to this action.

[0028] By setting the storage modulus of the binder resin contained in the coating agent within the above range, the heat resistance, suitability for bag making, and adhesion are improved. The factors for achieving the above-mentioned requirements for the storage modulus of the binder resin will be described in detail below.

[0029] <Embodiments that satisfy the storage modulus requirements of binder resin> As an embodiment that satisfies the above-mentioned requirements for the storage modulus of the binder resin, it is preferable to include a binder resin having a glass transition point of 120°C or higher, the binder resin preferably has a melting point of 140°C or higher, and the weight average molecular weight of the binder resin is preferably 8,000 to 70,000. Preferred examples of the binder resin include urethane resin, acrylic resin, epoxy resin, polyolefin resin, polyester resin, polyamide resin, polyimide resin, polyamideimide resin, cellulose resin, and composite resins obtained by combining these resins, and the binder resin may contain one or more of these. Among these, cellulose resins are preferred from the viewpoints of heat resistance and adhesion.

[0030] Examples of the cellulose-based resin include nitrocellulose, cellulose acetate, cellulose propionate, cellulose butyrate, methylcellulose, ethylcellulose, hydroxypropylcellulose, hydroxyethylcellulose, and carboxymethylcellulose, and are preferably one or more selected from the group consisting of nitrocellulose, cellulose acetate, cellulose propionate, and cellulose butyrate, more preferably one or more selected from the group consisting of nitrocellulose, cellulose propionate, and cellulose butyrate, and even more preferably nitrocellulose and / or cellulose acetate propionate. These cellulose-based resins may be used alone or in combination of two or more.

[0031] The type and viscosity symbol of nitrocellulose as defined by viscosity measurement in accordance with JIS K 6703:1995 are preferably H1 / 4, H1 / 8, H1 / 16, L1 / 4, and L1 / 8, and the viscosity of cellulose acetate propionate and cellulose acetate butyrate as measured by the viscosity measurement method described in ASTM-D1343-54T is preferably 0.05 to 3 seconds.

[0032] The content of cellulose-based resin in the coating agent is preferably 20% by mass or more out of 100% by mass of the solid content of the coating agent, the content of cellulose-based resin in the binder resin is preferably 60% by mass or more out of 100% by mass of the binder resin, and the content of nitrocellulose in the binder is preferably 60% by mass or more out of 100% by mass of the binder resin. The coating agent of the present invention is not limited to the above embodiment.

[0033] By setting the viscosity of the coating agent at a solid content of 26% by mass within the above range, the heat resistance, suitability for bag making, and adhesion are improved. The factors for achieving the viscosity requirement at a solids content of 26% by mass of the above-mentioned coating agent are described in detail below.

[0034] <Embodiments that meet the viscosity requirement at a coating agent solid content of 26% by mass> Typically, a solution of 26% solids by mass containing only the binder resin that satisfies the above storage modulus requirements has a viscosity of 1,100 to 10,000 mPa·s. However, a lower viscosity can be achieved by taking the following steps. As an embodiment that satisfies the viscosity requirement at a solids content of 26% by mass of the above-mentioned coating agent, it is preferable that the coating agent contains a binder resin having a glass transition point of 120°C or higher, the binder resin preferably has a melting point of 140°C or higher, and the weight average molecular weight of the binder resin is preferably 8,000 to 70,000.

[0035] Preferred examples of the binder resin include urethane resin, acrylic resin, epoxy resin, polyolefin resin, polyester resin, polyamide resin, polyimide resin, polyamideimide resin, cellulose resin, and composite resins obtained by combining these resins, and the binder resin may contain one or more of these. Among these, cellulose resins are preferred from the viewpoints of heat resistance and adhesion.

[0036] Examples of the cellulose-based resin include nitrocellulose, cellulose acetate, cellulose propionate, cellulose butyrate, methylcellulose, ethylcellulose, hydroxypropylcellulose, hydroxyethylcellulose, and carboxymethylcellulose, and are preferably one or more selected from the group consisting of nitrocellulose, cellulose acetate, cellulose propionate, and cellulose butyrate, more preferably one or more selected from the group consisting of nitrocellulose, cellulose propionate, and cellulose butyrate, and even more preferably nitrocellulose and / or cellulose acetate propionate. These cellulose-based resins may be used alone or in combination of two or more.

[0037] The type and viscosity symbol of nitrocellulose as defined by viscosity measurement in accordance with JIS K 6703:1995 are preferably H1 / 4, H1 / 8, H1 / 16, L1 / 4, and L1 / 8, and the viscosity of cellulose acetate propionate and cellulose acetate butyrate as measured by the viscosity measurement method described in ASTM-D1343-54T is preferably 0.05 to 3 seconds. The content of cellulose-based resin in the coating agent is preferably 20% by mass or more out of 100% by mass of the solid content of the coating agent, the content of cellulose-based resin in the binder resin is preferably 60% by mass or more out of 100% by mass of the binder resin, and the content of nitrocellulose in the binder is preferably 60% by mass or more out of 100% by mass of the binder resin. The coating agent of the present invention is not limited to the above embodiment.

[0038] The inclusion of fine particles is one of the factors for satisfying the viscosity requirement of the coating agent. As the fine particles, both organic fine particles and inorganic fine particles can be used, but inorganic fine particles are preferable from the viewpoint of heat resistance. As the fine particles, for example, inorganic fine particles such as extender pigments such as silica, calcium carbonate, barium sulfate, etc., metal oxides such as titanium oxide, zinc oxide, iron oxide, aluminum oxide, etc., and organic fine particles such as polyurethane resin, polynylon resin, polyacrylic resin, polysilicone resin, polystyrene resin, melamine resin, polyester resin, polyethylene resin, benzoguanamine resin, etc. can be included, and one or more of these can be included.

[0039] In order to satisfy the above-mentioned viscosity requirement, the average particle size of the fine particles as measured by a laser light scattering method is preferably 3,000 nm or less, the oil absorption of the fine particles as measured in accordance with JIS K5101-13-1 is preferably 100 ml / 100 g or less, the refractive index of the fine particles is preferably 2.5 or less, and the specific surface area of ​​the fine particles is preferably 100 m 2 / g or less, the content of the fine particles in the coating agent is preferably 1 to 90 mass% in 100 mass% of the solid content of the coating agent, and the ratio of the mass of the fine particles to 100 mass% of the binder resin is preferably 1 to 900 mass%. The coating agent of the present invention is not limited to the above embodiment.

[0040] As an embodiment that satisfies the viscosity requirement of the coating agent described above, the solvent may include, for example, a non-aromatic organic solvent such as a hydrocarbon solvent such as methylcyclohexane or ethylcyclohexane; a ketone solvent such as acetone, methyl ethyl ketone (MEK), or methyl isobutyl ketone; an ester solvent such as ethyl acetate, n-propyl acetate, or butyl acetate; an alcohol solvent such as methanol, ethanol, propanol, isopropanol (IPA), or butanol; or a glycol solvent such as ethylene glycol monomethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, propylene glycol monomethyl ether, or propylene glycol mono-n-propyl ether. The solvent may be appropriately selected in consideration of reducing the amount of solvent remaining in the coating after printing, and one type may be used alone, or two or more types may be used in combination. The content of the solvent is preferably 30 to 95 mass% in 100 mass% of the coating agent, more preferably 50 to 90 mass%, and particularly preferably 70 to 85 mass%. The coating agent of the present invention is not limited to the above embodiment.

[0041] As a particularly preferred embodiment that simultaneously satisfies the above-mentioned requirements for the storage modulus of the resin and the requirements for the viscosity of the coating agent, the resin is a nitrocellulose resin, and the fine particles are calcium carbonate and / or barium sulfate, the average particle diameter of the fine particles is 30 to 150 nm, the oil absorption of the fine particles is 50 ml / 100 g or less, and the specific surface area of ​​the fine particles is 50 m 2 / g or less. It is particularly preferred that the ratio of the mass of the fine particles to 100% by mass of the resin is 30 to 100% by mass, and that the solvent contains a glycol solvent.

[0042] <Binder resin> The binder resin has a storage modulus of 1.0 x 10 at 110°C measured according to JIS K 7244-4. 8 Pa or more, 1.0×10 8 ~1.0×10 10 Pa is preferably 3.0×108 ~5.0×10 9 Pa, more preferably 5.0×10 8 ~1.0×10 9 It is more preferable that the storage modulus at 130° C. is 1.0×10 Pa. 7 Pa or more, and 1.0×10 7 ~5.0×10 9 Pa, more preferably 5.0×10 7 ~1.0×10 9 More preferably, the temperature is 1.0×10 Pa. 8 ~5.0×10 8 It is particularly preferable that the storage modulus is within the above range. When the storage modulus is within the above range, the heat resistance, the suitability for bag making, and the adhesiveness are improved.

[0043] The loss modulus of the binder resin at 100°C measured according to JIS K 7244-4 is 1.0 x 10 8 It is preferable that the value is equal to or greater than 1.0×10 8 ~1.0×10 9 Pa is more preferably 1.0×10 8 ~5.0×10 8 It is more preferable that the loss modulus at 100° C. measured in accordance with JIS K 7244-4 is a lower value than the storage modulus at 110° C. measured in accordance with JIS K 7244-4. When the loss modulus is within the above range, the heat resistance, bag-making suitability, and adhesion are improved.

[0044] The binder resin preferably contains a resin having a glass transition point of 120°C or higher. The binder resin more preferably contains a resin having a glass transition point of 120°C to 220°C, further preferably contains a resin having a glass transition point of 130°C to 210°C, and particularly preferably contains a resin having a glass transition point of 140°C to 200°C. When the coating agent contains a resin having a glass transition point of 120°C or higher, excellent heat resistance is exhibited, and the heat resistance and bag-making suitability of the coating layer become good. In addition, when the binder resin contains a resin having a glass transition point of 220°C or lower, the coating layer adheres to the substrate, and therefore the adhesion and heat resistance are also good. The content of the resin having a glass transition point of 120°C to 220°C is preferably 50% by mass or more, more preferably 70% by mass or more, in 100% by mass of the binder resin.

[0045] Moreover, the binder resin preferably contains a resin having a melting point of 140°C or higher. The binder resin more preferably contains a resin having a melting point of 140°C to 250°C, further preferably contains a resin having a melting point of 150°C to 230°C, and particularly preferably contains a resin having a melting point of 160°C to 220°C. When the coating agent contains a resin having a melting point of 140°C or higher, excellent heat resistance is exhibited, and the heat resistance and bag-making suitability of the coating layer become good. When the binder resin contains a resin having a melting point of 250°C or lower, the coating layer adheres to the substrate, and therefore the adhesion and heat resistance are also good. The content of the resin having a melting point of 140°C to 250°C is preferably 50% by mass or more, more preferably 70% by mass or more, in 100% by mass of the binder resin.

[0046] The weight average molecular weight of the binder resin is preferably 8,000 to 70,000. More preferably, it is 9,000 to 50,000, and even more preferably, it is 10,000 to 40,000. When the weight average molecular weight of the binder resin is 8,000 or more, the heat resistance and bag-making suitability of the coating layer are improved. On the other hand, when the weight average molecular weight of the binder resin is 70,000 or less, the viscosity of the coating agent is appropriately controlled, and the printability is improved. The weight average molecular weight is measured by gel permeation chromatography (GPC).

[0047] The binder resin is preferably one that satisfies the above-mentioned viscoelastic properties among urethane resin, acrylic resin, epoxy resin, polyolefin resin, polyester resin, polyamide resin, polyimide resin, polyamideimide resin, cellulose-based resin, and composite resins obtained by combining these resins, and may contain one or more of these. Among these, cellulose-based resins are preferred from the viewpoints of heat resistance and adhesion. From the viewpoint of heat resistance and adhesion, it is also preferable to use a cellulose-based resin in combination with a polyamide resin.

[0048] <Cellulose-based resin> Examples of the cellulose-based resin include nitrocellulose, cellulose acetate, cellulose propionate, cellulose butyrate, methylcellulose, ethylcellulose, hydroxypropylcellulose, hydroxyethylcellulose, and carboxymethylcellulose, and are preferably one or more selected from the group consisting of nitrocellulose, cellulose acetate, cellulose propionate, and cellulose butyrate, more preferably one or more selected from the group consisting of nitrocellulose, cellulose propionate, and cellulose butyrate, and even more preferably nitrocellulose and / or cellulose acetate propionate. These cellulose-based resins may be used alone or in combination of two or more.

[0049] The content of the cellulose-based resin is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40 to 95% by mass, based on 100% by mass of the solid content of the coating agent. When the content of the cellulose-based resin is within the above range, the heat resistance and bag-making suitability of the coating layer are good.

[0050] The content of the cellulose-based resin is preferably 60% by mass or more, and more preferably 80% by mass or more, based on 100% by mass of the binder resin. When the content of the cellulose-based resin is within the above range, the heat resistance and bag-making suitability of the coating layer are good.

[0051] When the cellulose-based resin contains cellulose acetate propionate and / or cellulose acetate butyrate, the viscosity of the cellulose acetate propionate and cellulose acetate butyrate measured by the viscosity measurement method described in ASTM-D1343-54T is preferably 0.05 to 3 seconds, more preferably 0.1 to 1 second. When the viscosity of the cellulose acetate propionate and cellulose acetate butyrate is within the above range, excellent heat resistance is exhibited, and the heat resistance and bag-making suitability of the coating layer are improved. In addition, the viscosity of the coating agent is appropriately controlled, resulting in good printability.

[0052] When the cellulose-based resin contains cellulose acetate propionate, the content of cellulose acetate propionate is preferably 5 to 30 mass% and more preferably 5 to 20 mass% in 100 mass% of the binder resin. When the content of cellulose acetate propionate is 5 mass% or more, the heat resistance and the suitability for bag making are good, and the blocking resistance is good. When the content of cellulose acetate propionate is 30 mass% or less, the heat resistance and the suitability for bag making are good, and the adhesion is good.

[0053] When the cellulose-based resin contains nitrocellulose, the type and viscosity symbol of nitrocellulose as defined by viscosity measurement according to JIS K 6703:1995 are preferably H1 / 4, H1 / 8, H1 / 16, L1 / 4, and L1 / 8, and more preferably H1 / 8, H1 / 16, and L1 / 8. By using nitrocellulose with a type and viscosity symbol of H1 / 4, H1 / 8, H1 / 16, L1 / 4, and L1 / 8, excellent heat resistance is exhibited, and the heat resistance and bag-making suitability of the coating layer are improved. In addition, the viscosity of the coating agent is appropriately controlled, and the printing suitability is improved.

[0054] When the cellulose-based resin contains nitrocellulose, the content of nitrocellulose is preferably 60% by mass or more, more preferably 80% by mass or more, based on 100% by mass of the binder resin. When the content of nitrocellulose is within the above range, the heat resistance, bag-making suitability, and adhesion are good.

[0055] <Fine particles> The coating agent of the present invention contains fine particles. When the coating agent contains fine particles, the heat resistance and bag-making suitability of the coating layer formed are improved. Although both organic and inorganic fine particles can be used as the fine particles, inorganic fine particles are preferable from the viewpoint of heat resistance. Examples of the fine particles include inorganic fine particles such as extender pigments such as silica, calcium carbonate, and barium sulfate, metal oxides such as titanium oxide, zinc oxide, iron oxide, and aluminum oxide, and organic fine particles such as polyurethane resins, polynylon resins, polyacrylic resins, polysilicone resins, polystyrene resins, melamine resins, polyester resins, polyethylene resins, and benzoguanamine resins, and one or more of these may be contained. In particular, from the viewpoint of heat resistance and bag-making suitability, it is preferable that the fine particles are one or more selected from the group consisting of calcium carbonate, barium sulfate, titanium oxide, zinc oxide, aluminum oxide, and zirconium oxide, more preferably one or more selected from the group consisting of calcium carbonate, barium sulfate, and zinc oxide, and even more preferably calcium carbonate and / or barium sulfate.

[0056] The content of the fine particles is preferably 1 to 90% by mass, more preferably 10 to 80% by mass, and even more preferably 20 to 80% by mass, based on 100% by mass of the solid content of the coating agent. When the content of the fine particles is within the above range, the printability of the coating agent and the heat resistance and bag-making suitability of the formed coating layer are improved.

[0057] The content of the fine particles is preferably 1 to 900% by mass, more preferably 10 to 233% by mass, further preferably 20 to 150% by mass, and particularly preferably 30 to 100% by mass, relative to 100% by mass of the binder resin. When the content of the fine particles is within the above range, the heat resistance and bag-making suitability of the coating layer are improved.

[0058] The average particle size of the fine particles is preferably 3,000 nm or less, more preferably 10 to 1,000 nm, even more preferably 20 to 300 nm, and particularly preferably 30 to 150 nm. When the average particle size of the fine particles is within the above range, the heat resistance, bag-making suitability, and transparency are improved. The average particle size in the present invention is measured by a laser light scattering method, and the peak of the (histogram) in the obtained number particle size distribution is taken as the average particle size.

[0059] The oil absorption of the microparticles is preferably 100 ml / 100 g or less, more preferably 50 ml / 100 g or less, and even more preferably 30 ml / 100 g or less. When the oil absorption of the microparticles is within the above range, the heat resistance and bag-making suitability are improved. The oil absorption can be measured according to JIS K5101-13-1.

[0060] The refractive index of the fine particles is preferably not more than 2.5, more preferably not more than 2.0, and even more preferably not more than 1.8. When the refractive index of the fine particles is within the above range, the transparency is improved.

[0061] The specific surface area of ​​the particles is 100m 2 / g or less, and 2When the specific surface area of ​​the fine particles is in the above range, the heat resistance and the suitability for bag making are improved.

[0062] <Solvent> The coating agent of the present invention contains a solvent. Examples of the solvent include non-aromatic organic solvents such as hydrocarbons such as methylcyclohexane and ethylcyclohexane; ketones such as acetone, methyl ethyl ketone (MEK), and methyl isobutyl ketone; esters such as ethyl acetate, n-propyl acetate, and butyl acetate; alcohols such as methanol, ethanol, propanol, isopropanol (IPA), and butanol; and glycols such as ethylene glycol monomethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, propylene glycol monomethyl ether, and propylene glycol mono-n-propyl ether. The solvent may be appropriately selected in consideration of reducing the amount of solvent remaining in the coating after printing, and one type may be used alone, or two or more types may be used in combination. The content of the solvent is preferably 30 to 95 mass%, more preferably 50 to 90 mass%, and particularly preferably 70 to 85 mass% in 100 mass% of the coating agent. The coating agent of the present invention preferably contains a glycol solvent, which improves the dispersibility of the fine particles and the solubility of the binder resin, thereby improving the printability of the coating agent.

[0063] <Adhesion promoter> From the viewpoint of improving adhesion to the substrate, the coating agent preferably contains an adhesion promoter. Examples of the adhesion promoter include chlorinated polyolefins and acid-modified polyolefins, and chlorinated polyolefins are particularly preferred.

[0064] <Chlorinated polyolefin> The chlorine content of the chlorinated polyolefin is preferably 5 to 60 mass%, more preferably 10 to 50 mass%, and even more preferably 20 to 40 mass% in 100 mass% of the chlorinated polyolefin. Here, the chlorine content in the present invention refers to the mass% content of chlorine atoms in 100 mass% of the chlorinated polyolefin. In addition, from the viewpoint of solubility in a mixed solvent of an ester solvent and an alcohol solvent, the weight average molecular weight of the chlorinated polyolefin is preferably 5,000 to 80,000, and more preferably 8,000 to 50,000.

[0065] In the present invention, the chlorinated polyolefin has a structure in which hydrogen atoms in an α-olefin polymer represented by the following general formula (1) are substituted with chlorine atoms. General formula (1) CH2=CH-R (wherein R is an alkyl group having one or more carbon atoms)

[0066] The chlorinated polyolefin preferably has a flexible alkyl group as a branched structure, which allows it to remain viscous even at low temperatures and improves the adhesion of the coating layer to the substrate. There are no particular limitations on the polyolefin structure in the chlorinated polyolefin, but resins containing homopolymers or copolymers of α-olefin-based unsaturated hydrocarbons such as polypropylene, poly-1-butene, and poly-4-methyl-1-pentene are preferred. Among these, those containing a polypropylene structure (i.e., a chlorinated polypropylene structure) are particularly preferred.

[0067] The content of the chlorinated polyolefin is preferably 0.5 to 5%, more preferably 0.8 to 4%, and even more preferably 1.0 to 3% in 100% by mass of the solid content of the coating agent. When the content of the chlorinated polyolefin is within the above range, the adhesion of the coating layer to the substrate is improved.

[0068] <Additives> The coating agent of the present invention may contain any additives, such as a plasticizer, an amide wax, a hydrocarbon wax, a chelating crosslinking agent, etc. The coating agent preferably does not contain a visible light absorbing dye, which makes it possible to improve the heat resistance while maintaining the high transparency of the coating layer.

[0069] <Method of manufacturing coating agent> The coating agent of the present invention contains the above-mentioned binder resin, fine particles, and solvent, and further, in order to improve the handling, heat resistance, and bag-making suitability of the coating agent, the above-mentioned adhesion imparting agent, other additives, and other optional components can be added to the coating agent, either alone or in combination. The coating agent can be obtained, for example, by feeding a binder resin solution in which a binder resin is dissolved in an organic solvent and / or fine particles, and an organic solvent into a stirrer equipped with a stirring blade, a rotor, or the like, and mixing and stirring them. The stirring speed is not particularly limited, and can be performed at 50 to 30,000 rpm.

[0070] <Laminate> A laminate can be produced by using the coating agent of the present invention. The laminate can have a coating layer made of the coating agent of the present invention on a substrate 1 described later. A preferred embodiment has an adhesive layer and a substrate 2 described later on the substrate 1 in this order, and further has a coating layer made of the coating agent of the present invention. The method for forming the coating layer in the laminate is not particularly limited, and the coating layer can be formed by printing the coating agent on the substrate 1 and / or substrate 2 by a known printing method and removing the volatile components. The laminate having a coating layer made of the coating agent of the present invention is preferably a packaging material used for packaging foods, beverages, daily necessities, medicines, and the like.

[0071] <Layer structure> Specific examples of the structure of the laminate having a coating layer made of the coating agent of the present invention include, but are not limited to, the following structures. In the structures (1) to (4) below, " / " indicates the boundary between layers. (1) Coating layer / substrate 1 / adhesive layer / substrate 2 (2) Substrate 1 / coat layer / adhesive layer / substrate 2 (3) Substrate 1 / adhesive layer / coating layer / substrate 2 (4) Coating layer / substrate 1

[0072] <Base material 1> The substrate 1 is not particularly limited, but is preferably a polyolefin resin. Suitable examples of the polyolefin resin include polypropylene such as biaxially oriented polypropylene (OPP), non-oriented polypropylene (CPP), acid-modified polypropylene, and copolymerized polypropylene, polyethylene such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), and acid-modified polyethylene, and films laminated with these, among which low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE) are preferred. The thickness of the substrate 1 is not particularly limited, and is preferably 5 μm or more and 150 μm or less, and more preferably 10 μm or more and 70 μm or less.

[0073] The substrate 1 and the substrate 2 described later may be a single layer, may be simply laminated with each other, or may be laminated with a substrate different from the plastic substrate via an adhesive layer or the like. The "substrate different from the plastic substrate" may be a plastic substrate or a paper substrate having different properties, and may be of any type. The method of laminating the substrates is not particularly limited, and may be a conventionally known method such as a co-extrusion method, heat fusion, or pressure bonding via an adhesive layer.

[0074] The substrate 1 and the substrate 2 described below preferably contain additives such as antistatic agents, antifogging agents, and ultraviolet protection agents by coating or kneading, have an easily adhesive coating layer (e.g., a layer containing polyvinyl alcohol and / or its derivatives), have a surface of the substrate subjected to corona treatment or low-temperature plasma treatment, etc. The above-mentioned additions and processing are also carried out for the purpose of improving the wettability of printing inks and other coating agents, or for the purpose of imparting specific functionality to the film, and are preferably used, for example, to provide a packaging material with excellent visibility of the contents by preventing the packaging material from fogging due to moisture.

[0075] <Adhesive layer> The components of the adhesive layer are not particularly limited, and suitable examples include dry lamination adhesives or non-solvent lamination adhesives such as olefin-based adhesives, acrylic adhesives, ethylene-vinyl acetate copolymer adhesives, reactive urethane adhesives, imine-based anchor coating agents, butadiene-based anchor coating agents, isocyanate-based anchor coating agents, and thermoplastic resins used in extrusion lamination. The adhesive layer preferably contains a reaction product of a reactive urethane adhesive consisting of a polyisocyanate and a polyol. The adhesive layer may contain an inorganic compound for the purpose of improving the barrier properties of the packaging material. The thickness of the adhesive layer is preferably 0.5 μm or more and 20 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1.0 μm or more and 4.5 μm or less.

[0076] <Method of forming adhesive layer and method of bonding each layer> The method for forming the adhesive layer and the method for bonding each layer are not particularly limited, and may be any of the conventionally known methods such as extrusion lamination, dry lamination, and non-solvent lamination.

[0077] <Base material 2> The substrate 2 preferably contains a polyolefin resin, which may be the same as or different from the substrate 1, but is preferably a sealant layer. The sealant layer refers to a layer having heat sealability. The substrate 2 is preferably the outermost layer of the packaging material. The description of the substrate 1 above can be used for the polyolefin resin contained in the substrate 2. The thickness of the substrate 2 is preferably 20 to 200 μm, more preferably 20 to 100 μm, and even more preferably 20 to 60 μm.

[0078] <Ink layer> The laminate having a coating layer made of the coating agent of the present invention may have an ink layer for the purpose of imparting a chromatic color, and the ink layer contains a resin and a colorant. The ink layer may be a layer that displays any design, pattern, letter, symbol, etc. for the purpose of providing decoration or aesthetics; displaying the contents, expiration date, and manufacturer or seller. The ink layer may be a solid ink layer that does not have a design, pattern, letter, symbol, etc. The method for forming the ink layer is not particularly limited, and it can be formed using a printing ink. In addition, the ink layer may be a single layer or a multi-layer structure, and may be printed on the surface layer of the laminate. The mass per unit area of ​​the ink layer is 0.1 to 12 g / m 2 It is preferable that the thickness is 0.5 to 6 g / m 2 More preferably, it is 1 to 3 g / m 2 It is more preferable that:

[0079] <Deposition layer and barrier layer> The laminate having a coating layer made of the coating agent of the present invention may have a deposition layer and / or a barrier layer for the purpose of controlling the gas permeability of the film. The deposition layer exists for the purpose of imparting oxygen barrier properties and / or water vapor barrier properties to the packaging material, and examples thereof include deposition layers made of metal oxides such as aluminum oxide, silicon oxide, magnesium oxide, and tin oxide. The barrier layer exists mainly for the purpose of imparting oxygen barrier properties to the packaging material, and preferably contains a polyvinyl alcohol-based resin. The form of the barrier layer may be any known form, but it is preferably a barrier coat layer formed by a barrier coating agent.

[0080] <Intermediate substrate> The packaging material using the coating agent of the present invention may have an intermediate substrate. A specific example of the intermediate substrate is preferably a plastic substrate mainly containing polyolefin resin as a raw material, similar to the substrate 1 and substrate 2. Examples of the intermediate substrate include polyolefin resins such as low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), ethylene-vinyl acetate copolymer, propylene homopolymer, and ethylene-propylene copolymer. The intermediate substrate may also be a composite substrate produced by a co-extrusion method. Furthermore, the intermediate substrate is preferably made of the same (same) material as the substrate 1 and / or substrate 2, and more preferably made of the same (same) material as the substrate 1 and substrate 2. Examples of the same (same) material include a combination of polypropylene and polyethylene, etc. EXAMPLES

[0081] The present invention will be described below with reference to examples, but the present invention is not limited thereto. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.

[0082] <Storage modulus and loss modulus> The storage modulus and loss modulus were measured based on JIS K 7244. That is, the coating agent was centrifuged to extract only the resin component, and the obtained resin component was used to form a test piece with a thickness of 100 μm. Using the obtained test piece, dynamic viscoelasticity measurement was performed based on JIS K 7244 under conditions of a frequency of 1.0 Hz, a temperature of 25 to 250°C, and a heating rate of 5°C / min.

[0083] <Viscosity measurement> The viscosity of the coating agent was measured in accordance with JIS K 7117-1 using a Toki Sangyo Viscometer TUB-10 under the following conditions. If the solid content was higher than 26%, it was adjusted to 26% by diluting with a mixed solvent (ethyl acetate / isopropanol = 50 / 50), and if it was lower, the solid content was adjusted to 26% by opening the lid of the storage container of the coating agent and leaving it to stand to evaporate the solvent. The rotor used was M1 when the viscosity of the coating agent was less than 1000 mPa·s, and M2 when it was 1000 mPa·s or more. Measurement conditions Rotor: M1 (viscosity less than 1000 mPa·s) or M2 (viscosity 1000 mPa·s or more) Rotational speed: 6 rpm Liquid temperature: 25℃ ·Solid content 26% by mass

[0084] <Glass transition point and melting point> The glass transition point of the binder resin was measured by DSC (differential scanning calorimeter manufactured by TA Instruments). Specifically, about 2 mg of a sample obtained by drying the coating agent was weighed on an aluminum pan, the aluminum pan was set in a DSC measurement holder, and the baseline shift to the highest endothermic temperature side in the DSC curve obtained under the temperature rise condition of 5°C / min was read to obtain the glass transition point. In addition, the endothermic peak on the highest temperature side between 140°C and 250°C was read, and the peak temperature was taken as the melting point.

[0085] <Weight average molecular weight> The weight average molecular weight of the resin was determined by measuring the molecular weight distribution using a gel permeation chromatography (GPC) device (HLC-8220 manufactured by Tosoh Corporation) and calculating the molecular weight converted using polystyrene as a standard substance. The measurement conditions are shown below. Columns: The following columns were used in series connection: Tosoh Corporation TSKgel Super AW2500 Tosoh Corporation TSKgel Super AW3000 Tosoh Corporation TSKgel Super AW4000 Tosoh Corporation's TSK gelguard column Super AWH Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 1.0mL / min

[0086] <Heat shrinkage rate> The packaging material was cut into a size of 50 mm x 25 mm (when the substrate contained a uniaxially stretched film, the long side was set to 50 mm in the stretching direction), and using a heat seal tester, heat and pressure were applied to an area of ​​20 mm x 10 mm as shown in Figures 1 and 2, and calculations were made using the following formula 1. The heat and pressure conditions were heating temperature: 145°C, pressure: 2 kg, and heating and pressure time: 1 second. (Formula 1) Shrinkage rate (area%) = {1-(area after heating and pressing) / (area before heating and pressing)} x 100

[0087] <Chlorine content> The chlorine content was measured in accordance with JIS K0127 (2013). That is, the coating agent, binder resin, or adhesion promoter was each applied to a transparent substrate to a thickness of 2.0 μm to form a coating film. After drying at 80°C, 0.5 g was scraped off. The scraped off coating film was pretreated by a combustion method, and the chlorine content of the obtained sample was quantified by ion chromatography to determine the chlorine content.

[0088] <Production of urethane resin> [Synthesis Example 1] Urethane resin PU1 100 parts of polyester polyol having a number average molecular weight of 2,000, which is a condensation product of 3-methyl-1,5-pentanediol and sebacic acid, 1 part of 1,4-butanediol, 28.5 parts of isophorone diisocyanate, and 32.1 parts of ethyl acetate were mixed and reacted under a nitrogen atmosphere at 90°C for 5 hours to obtain a urethane prepolymer with a terminal isocyanate. Next, 11.0 parts of isophoronediamine, 1.0 parts of N-(2-aminoethyl)ethanolamine, 1.0 parts of dibutylamine, and 298.1 parts of mixed solvent 1 (ethyl acetate / isopropanol=70 / 30 (mass ratio)) were stirred and mixed, and the obtained urethane prepolymer with terminal isocyanate was gradually added at 40° C. The mixture was reacted at 80° C. for 1 hour to obtain a solution of urethane resin PU1 with a solid content of 30 mass%, an amine value of 6.5 mg KOH / g, a hydroxyl value of 3.8 mg KOH / g, and a weight average molecular weight of 50,000. The chlorine content of the urethane resin PU1 was 0 mass%.

[0089] <Production of coating agents> [Example 1] Coating agent 1 Barium sulfate A (average particle size 50 nm, solid content 100%, oil absorption 20 ml / 100 g, refractive index 1.64) 5.0 parts, BYK-111 (resin having acidic functional groups manufactured by BYK-Chemie, solid content 95%) 0.1 parts, ethyl acetate 8.0 parts, 2-propanol 1.0 parts, propylene glycol monomethyl ether 1.0 parts were stirred and mixed, dispersed with a bead mill (using zirconia beads), and then nitrocellulose resin solution DHX3-5 (ICI Novel Enterprises nitrocellulose, nitrogen content 12.0%, solid content 30%, 2-propanol solution) 16.2 parts, CAP-504-0.2 solution (Eastman Cellulose Acetate Propionate Glass Transition Point 159 ° C, Melting Point 188 ° C, Weight Average Molecular Weight 15,000, Solid Content 30%) 1.8 parts, Super Chron 370M (Nippon Paper Industries Co., Ltd. 0.4 parts of chlorinated polypropylene and 0.1 parts of CERAFLOUR 925N (a wax additive manufactured by BYK) were mixed with stirring to obtain coating agent 1. Cellulose acetate propionate (CAP) was prepared by preparing a resin solution with a solid content of 30% in a mixed solvent of ethyl acetate / 2-propanol / propylene glycol monomethyl ether (8 / 1 / 1).

[0090] [Examples 2 to 26, Comparative Examples 1 to 5] Coating Agents 2 to 31 Coating agents 2 to 31 were obtained in the same manner as in Example 1, except that the raw materials and compounding ratios were changed to those shown in Table 1. The cellulose acetate propionate (CAP) used was a resin solution in which the solid content was adjusted to 30% using a mixed solvent of ethyl acetate / 2-propanol / propylene glycol monomethyl ether=8 / 1 / 1.

[0091] Details of the raw materials in Table 1 are shown below. ·Barium sulfate B (average particle size: 150nm, solid content 100%, oil absorption 20ml / 100g, refractive index 1.64) ·Barium sulfate C (average particle size: 350nm, solid content 100%, oil absorption 20ml / 100g, refractive index 1.64) Barium sulfate D (average particle size: 1 μm, solid content 100%, oil absorption 17 ml / 100 g, refractive index 1.64) Barium sulfate E (average particle size: 2.8 μm, solid content 100%, oil absorption 15 ml / 100 g, refractive index 1.64) Barium sulfate F (average particle size: 5 μm, solid content 100%, oil absorption 13 ml / 100 g, refractive index 1.64) Calcium carbonate (average particle size 50 nm, solid content 100%, oil absorption 46 ml / 100 g, refractive index 1.6) Zinc oxide: (average particle size 100 nm, solid content 100%, oil absorption 32 ml / 100 g, refractive index 1.9) Titanium oxide (average particle size: 100 nm, solid content 100%, oil absorption 28 ml / 100 g, refractive index 2.52) Aluminum oxide (average particle size: 100 nm, solid content 100%, oil absorption 37 ml / 100 g, refractive index 1.63) ·Silica (average particle size: 5μm, solid content 100%, oil absorption 90ml / 100g, refractive index 1.43) Zirconium oxide (average particle size: 100 nm, solid content 100%, oil absorption 31 ml / 100 g, refractive index 2.17) Urethane resin particles: Artvar C-600 (manufactured by Negami Chemical Industries, Tg-13℃, average particle size 10μm) Carbon black (average particle size 600 nm, solid content 100%, oil absorption 140 ml / 100 g) Leomaid S-8200: Polyamide resin manufactured by Kao Corporation, melting point 108-116°C, weight average molecular weight 3500 (solid content 30% 2-propanol / toluene = 30 / 70 solution) DHX3-5: Nitrocellulose manufactured by Inabata & Co., Ltd. Standard H1 / 16 HR-15ET: Polyamide-imide resin manufactured by Toyobo MC, glass transition temperature 260°C, weight average molecular weight 6,000 CAP-504-0.2: Cellulose acetate propionate manufactured by Eastman Co., glass transition point 159°C, melting point 188°C, weight average molecular weight 15,000

[0092] <Production of Laminate> The coating agents obtained in the examples and comparative examples were diluted with a mixed solvent (isopropyl alcohol / ethyl acetate) to a viscosity of 16 seconds in Zahn cup #3. The diluted coating agent was then printed on the corona-treated surface of a uniaxially oriented polyethylene (MDOPE) film (thickness 25 μm) that had been corona-treated on both sides using a gravure printing machine equipped with a gravure plate with a plate depth of 60 μm at a printing speed of 50 m / min and an in-line oven temperature of 60°C to form a coating layer, thereby obtaining laminates having a coating layer / substrate configuration.

[0093] <Evaluation of the laminate> The obtained laminate was evaluated as follows, and the results are shown in Table 1.

[0094] [Heat resistance] The laminate was cut into a piece of 50 mm x 25 mm, and heated and pressed under the conditions below in a 20 mm x 10 mm area as shown in Figures 1 and 2 using a heat seal tester, and the appearance change of the laminate was evaluated. <Heating and pressurizing conditions> Heating temperature: 160℃, pressure: 2kg, heating and pressure time: 1 second, Heating and pressing direction: Heating and pressing were applied from the coating layer side of the packaging material. For Examples 21 and 22 in which the coating layer was not the outermost layer, heating and pressing were applied from the substrate 1 side. (Evaluation Criteria) S: No noticeable wrinkles in the heated and pressed area (very good). A: Wrinkles appear in the heated and pressurized area, but the film is not melted or broken. (Good) B: Wrinkles have appeared in the heated and pressurized area, and the film has partially melted and broken. (Can be used) C: The heat and pressure applied part is completely melted and separated. (Not suitable for use)

[0095] [Bag making suitability] A 30 m long, 12.5 cm wide packaging material was marked every 1 m and then heated and pressurized 30 times per 1 m length under the conditions below using a three-side sealed automatic bag making machine, and the shrinkage rate in the longitudinal direction of the laminate was evaluated. <Heating and pressurizing conditions> Heating temperature: 145℃, pressure: 2kg, heating and pressure time: 1 second, Heating and pressing direction: Heating and pressing were applied from the coating layer side of the laminate. (Evaluation Criteria) S: The shrinkage rate in the longitudinal direction is less than 2.5%. (Very good) A: The shrinkage rate in the longitudinal direction is 2.5% or more and less than 5%. (Good) B: The shrinkage rate in the longitudinal direction is 5% or more and less than 10%. (Usable) C: The shrinkage rate in the length direction is 10% or more, or the film is melted. (Not for use)

[0096] [Adhesion] Based on JIS K5600-5-6, the packaging materials were subjected to an adhesion test using the cross-cut method and evaluated according to the following criteria. (Evaluation Criteria) S: The result of the adhesion test is in the category of 0 to 1. That is, the peeled area is less than 5%. A: The result of the adhesion test is Class 2. That is, the peeled area is 5% or more and less than 15%. B: The result of the adhesion test is Class 3. That is, the peeled area is 15% or more and less than 35%. C: The result of the adhesion test is category 4 to 5. That is, the peeled area is 35% or more.

[0097] [Transparency] The coating agents obtained in the Examples and Comparative Examples were applied to a uniaxially oriented polyethylene (MDOPE) film (thickness 25 μm) that had been corona-treated on both sides and printed with black bands using black ink, using a bar coater to apply the coating agents so that the thickness after drying would be 1.0 μm. The coating was then dried at 60° C. for 1 minute to form a coating layer, which was then evaluated according to the following criteria. (Evaluation Criteria) S: The black belt is clearly visible. (Very good) A: The black belt appears slightly white. (Good) B: The black belt is slightly visible. (Usable) C: The black belt is completely invisible. (Not available)

[0098] [Table 1]

[0099] [Table 1]

[0100] From the above results, Comparative Example 1 had poor heat resistance and bag-making suitability because the storage modulus of the binder resin did not satisfy the range of the present invention. Comparative Examples 2 and 3 had poor heat resistance and bag-making suitability because the viscosity of the coating agent when the solid content was 26% by mass did not satisfy the range of the present invention. Comparative Example 4 did not contain fine particles and had poor heat resistance, bag-making suitability, and adhesion because the viscosity of the coating agent when the solid content was 26% by mass did not satisfy the range of the present invention. On the other hand, the examples contained resin, fine particles, and a solvent, and the storage modulus of the binder resin and the viscosity when the coating agent had a solid content of 26 mass % were within the ranges of the present invention, so that the examples had good heat resistance, suitability for bag making, adhesion, and transparency.

Claims

1. A coating agent comprising a binder resin, fine particles and a solvent, The storage modulus of the binder resin at 110° C. measured in accordance with JIS K 7244-4 is 1.0×10 8 Pa or more, The coating agent has a viscosity of 1,000 mPa·s or less when the solid content of the coating agent is 26% by mass, as measured in accordance with JIS K 7117-1.

2. The loss modulus of the binder resin at 100° C. measured in accordance with JIS K 7244-4 is 1.0×10 8 The coating agent according to claim 1, wherein the viscosity is 100 Pa or more.

3. 3. The coating agent according to claim 1, wherein the fine particles are inorganic fine particles.

4. 4. The coating agent according to claim 3, wherein the inorganic fine particles contain at least one selected from the group consisting of calcium carbonate, barium sulfate, titanium oxide, zinc oxide, aluminum oxide, and zirconium oxide.

5. 3. The coating agent according to claim 1, wherein the fine particles have an average particle size of 3,000 nm or less as measured by a laser light scattering method.

6. 3. The coating agent according to claim 1, wherein a mass ratio of the fine particles to 100 mass% of the binder resin is 1 to 900 mass%.

7. The coating agent according to claim 1 or 2, wherein the binder resin comprises a cellulose-based resin.

8. The coating agent according to claim 1 or 2, wherein the solvent comprises a glycol-based solvent.

9. The coating agent according to claim 1 or 2, further comprising a chlorinated polyolefin.

10. The coating agent according to claim 1 or 2, which is used for suppressing thermal shrinkage of a substrate.

11. A packaging material having a coating layer made of the coating agent according to claim 1 or 2 on a substrate 1.

12. A packaging material comprising a substrate 1, an adhesive layer and a substrate 2 in this order, and further comprising a coating layer made of the coating agent according to claim 1 or 2.

Citation Information

Patent Citations

  • Gravure black ink composition for paper and printed matter using the composition

    JP2015101688A

  • Coating agent and use of the same

    JP2015214673A

  • Coating agent composition for printing and printed matter

    JP2017171910A

  • Matte coating agent, matte coated layer and laminate film

    JP2018070847A